UNI-ABODES: house rental apps for university students / Muhammad Ibrahim Faridon ... [et al.] - Faridon, Muhammad Ibrahim; Mohd Shafee, Nur Faeizah; Zuharzam, Nur Fareeha; Noor Jamal, Nor Azrin Shamira; Mohamed, Munirah (Universiti Teknologi MARA, Kedah, 2023)
UNI-ABODES is an innovative app specifically designed for university students to find a house or apartment to rent. With just a few taps on their smartphones, students can now browse through a wide range of housing options, compare prices and amenities, and connect with potential landlords or roommates. Students are having difficulty finding a place to live before the semester begins. Due to the limited space available in the hostel, they are compelled to find a place to rent outside of it. Aside from that, looking for house rentals can be a time-consuming procedure, and most students are clueless about where to look for rental housing. Our app’s objective is to provide university students with a reliable and friendly platform to meet their requirements. The novelty of this app is that it is designed to be tailored to a specific user demographic, which is university students, by considering factors such as location, budget constraints, roommates’ preferences, and proximity to campus. Besides, it caters to university students' requirements in Malaysia. This app significantly reduces the time and effort required by university students to find rental properties. Additionally, these apps allow students to focus more on their studies, and by accessing house rental apps, it can be a centralised platform to easily search and explore a wide range of rental listings. UNI-ABODES has the potential to be commercialized by considering the demand for student housing and integrating value-added services within the app that cater to the specific needs of university students, such as cleaning services and the use of Google Maps as a location search tool.